Emergence of a New Written Culture: The use of Hebrew script among the Krimchaks and the Karaim - Olach, Zsuzsanna (Acta Orientalia Vilnensia, 2017)
Conversion to a religion usually has a positive impact on the written culture of a given community. The conversion may or may not result in the adoption of a new writing system. In the Turkic world, we find examples for both cases. The Karaims, by their conversion into Karaitism, adopted the Hebrew script. They used the Hebrew alphabet up till the beginning of the 20th century in their everyday life for writing; for example, private letters and secular and religious texts in Karaim. Another Turkic speaking group, the heterogeneous Rabbanite community of Krimchaks (whose majority is of Sephardic origin) also used the Hebrew script to write their vernacular. Some characteristics of the writing systems of the Karaim and of the Krimchaks have been described, but no comparative research has thus far been carried out. In this study, the peculiarities of the Hebrew alphabet used by both Turkic speaking peoples will be discussed and illustrated. For instance, the new characters, which were introduced in order to indicate specific Turkic phonetic values, and the ways the same Hebrew vowel sign or letter is used in the different Krimchak and Karaim manuscripts.